Trilepton signal for supersymmetry at the Fermilab Tevatron reexamined - Baer, H.; Drees, M.; Paige, F.; Quintana, P.; Tata, X (American Physical Soc, 2000)
Within a wide class of models, the CERN LEP2 lower limit of 95 GeV on the chargino mass implies gluinos are heavier than similar to 300 GeV. In this case electroweak (W) over tilde(1)(W) over tilde(1) production and (W) over tilde(1)(Z) over tilde(2) production are the dominant supersymmerry (SUSY) processes at the Fermilab Tevatron, and the extensively examined isolated trilepton signal From (W) over tilde(1)(Z) over tilde(2) production assumes an even greater importance. We update our previous calculations of the SUSY reach of luminosity upgrades of the Fermilab Tevatron in this channel incorporating (i) decay matrix elements in the computation of the momenta of leptons from chargino and neutralino decays, (ii) the trilepton background from W*Z* and W*gamma* production which, though neglected in previous analyses, turns out to be the dominant background, and finally, (iii) modified sets of cuts designed to reduce these new backgrounds and increase the range of model parameters for which the signal is observable. We show our improved projections for the reach for SUSY of both the Fermilab Main Injector and the proposed TeV33 upgrade. We also present opposite sign same flavor dilepton invariant mass distributions as well as the p(T) distributions of leptons in SUSY trilepton events, and comment upon how the inclusion of decay matrix elements impacts upon the Tevatron reach, as well as upon the extraction of neutralino masses.